The Role of Calpains in Skeletal Muscle Remodeling with Exercise and Inactivity-induced Atrophy - Hyatt, Hayden W.; Powers, Scott K. (International Journal of Sports Medicine, 2020)
Calpains are cysteine proteases expressed in skeletal muscle fibers and other cells. Although calpain was first reported to act as a kinase activating factor in skeletal muscle, the consensus is now that calpains play a canonical role in protein turnover. However, recent evidence reveals new and exciting roles for calpains in skeletal muscle. This review will discuss the functions of calpains in skeletal muscle remodeling in response to both exercise and inactivity-induced muscle atrophy. Calpains participate in protein turnover and muscle remodeling by selectively cleaving target proteins and creating fragmented proteins that can be further degraded by other proteolytic systems. Nonetheless, an often overlooked function of calpains is that calpain-mediated cleavage of proteins can result in fragmented proteins that are biologically active and have the potential to actively influence cell signaling. In this manner, calpains function beyond their roles in protein turnover and influence downstream signaling effects. This review will highlight both the canonical and noncanonical roles that calpains play in skeletal muscle remodeling including sarcomere transformation, membrane repair, triad junction formation, regulation of excitation-contraction coupling, protein turnover, cell signaling, and mitochondrial function. We conclude with a discussion of key unanswered questions regarding the roles that calpains play in skeletal muscle.
Keywords: calpain; disuse atrophy; proteolysis; muscle remodeling; membrane repair; exercise